2015
DOI: 10.1155/2015/850245
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Cold Patch for Relieving Pain after Transepithelial Photorefractive Keratectomy

Abstract: Although photorefractive keratectomy often results in better corneal stability and fewer corneal flap complications than LASIK, pain remains a major drawback of the procedure. The authors compared the safety and efficacy of a postoperative cold patch versus intraoperative application of a chilled balanced salt solution on transepithelial photorefractive keratectomy-related postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In our collective clinical experience, use of an ice or cold pack can be very effective in relieving the pain associated with corneal abrasion or following procedures such as PRK and corneal collagen cross-linking. This is supported by results from a randomised controlled trial by Zeng et al 15 In this study, the simple application of a cold patch was found to be effective in reducing pain on a visual analogue scale as well as significantly reducing the use of LA drops and non-opioid oral analgesia following PRK.…”
Section: Alternative Options For Analgesia In Patients With Corneal Painsupporting
confidence: 63%
“…In our collective clinical experience, use of an ice or cold pack can be very effective in relieving the pain associated with corneal abrasion or following procedures such as PRK and corneal collagen cross-linking. This is supported by results from a randomised controlled trial by Zeng et al 15 In this study, the simple application of a cold patch was found to be effective in reducing pain on a visual analogue scale as well as significantly reducing the use of LA drops and non-opioid oral analgesia following PRK.…”
Section: Alternative Options For Analgesia In Patients With Corneal Painsupporting
confidence: 63%
“…Irrigating the ocular surface with chilled saline may be uncomfortable or even painful for the patient (Neuffer et al., 2013). Cold compresses using ice packs can be difficult to use, especially in the disabled or elderly populations, as movement is limited and frostbite is possible if not correctly used (Zeng et al., 2015). A recent report concluded that cryotherapy provides efficient and efficacious mitigation for IVI‐related pain (Chandrasekaran et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For example, application of a cold pack to the eye for 24 hours after PRK was associated with decreased pain scores at 8 hours, 16 hours, and 24 hours, in addition to decrease in use of pain medication. 52 It should be noted that application of cold packs is associated with ocular physiologic changes, which, in particular, may adversely affect certain patient populations (eg, angle-closure glaucoma). 53…”
Section: Emerging and New Therapeuticsmentioning
confidence: 99%